Application of ASP-NET technology based on B/S architecture in teacher management system - Ming Dong; Rui Pan (Discover Artificial Intelligence)
Abstract It is the realistic choice and inevitable trend of modern education development to change the traditional education mode through information technology and then promote the modernization of education with education informatization. Aiming to address the problems in applying B/S architecture in teaching management systems, this paper uses ASP-NET technology to optimize. In this paper, an improved Fp-growth algorithm is proposed to mine data association rules by using the improved Fp-growth algorithm. Experiments on Web Docs, accidents, and bio-train databases show that the performance of the improved algorithm is better than the original algorithm. The design of a teacher management system based on ASP-NET technology covers system framework (using a B/S three-layer structure), module design (for administrators, teachers, students, and other user types design functions), database design, and teacher data association mining. Finally, the teacher management system is tested, and it is found that when the minimum confidence support is small or the database is large, the Fp-Growth algorithm needs a very large memory when used alone. However, the improved database partitioning strategy overcomes this defect, significantly reduces the occupied memory, and results in a higher mining speed than Fp-Growth. In the process of increasing the number of users from 100 to 300, the CPU usage only increased by 20%, the memory usage increased by 26%, the system compatibility in this paper is strong, and the required device resources are less. When the test time is extended, the number of concurrent users increases, and the process has a certain regularity, indicating that the test process is very smooth. There is no obvious error in the system. When the test time was extended, the response time of the teacher management system changed, but the longest response time was within 0.12 s, which was consistent with the expected result. The fastest response time is only about 0.03 s, the overall response time is stable, and the fluctuation range is small. It shows that the teacher management system proposed in this paper has good robustness.